Spatial Patterns of Tourism: Towards Legally-Based Tourism Village Regulations Based on Physical Carrying Capacity Analysis - Darwis, Darwis; Jasman, Jasman; Apriyanto, Bejo; Mandalia, Siska; Widjaja, Herry Rachmat; Ridwan, Masri (Geosfera Indonesia, 2024)
Lowita Beach was a tourist area in Suppa District, Pinrang Regency, with 11 tourist attractions. The annual increase in visitors to Lowita Beach can compromise tourist comfort and damage the area's natural habitat. This is the basis for researchers to analyse the Physical Carrying Capacity (PCC) of Lowita Beach. This study aimed to determine the characteristics of tourist activities, assess the physical carrying capacity of the area, and formulate the role of tourist villages in managing the Lowita Beach area. The research approach used was research and development, as initiated by Borg and Gall: the calculation of Physical Carrying Capacity (PCC), area parameters, and the number of tourists. The study population comprised 93 tourists who visited the Lowita Beach area. Data was collected through the completion of questionnaires, interviews, measurements, and field observations. A quantitative-descriptive approach was used for data analysis. The Physical Carrying Capacity (PCC) analysis reveals that Lowita Beach's ideal capacity is 1 visitor per day, yet it currently hosts an average of 35 visitors daily, significantly surpassing this threshold. This overcapacity indicates that the beach is experiencing environmental strain and underscores the need for management strategies to align visitor numbers with sustainable limits. In conclusion, despite the physical carrying capacity (PCC) of Lowita Beach being 17 visitors per day, the present daily visitor count suggests that the beach is currently facing overcrowding, albeit not to a significant extent. Hence, it is necessary to implement policy interventions from the tourist villages of Tasiwalie and Wiringtasi, which should include the establishment of standardized operating procedures and fostering collaboration among stakeholders, in order to ensure sustainable tourism management at Lowita Beach.